Nilai-Nilai Pendidikan Islam Dalam Kegiatan Hadrah Ar-Rasyidin Desa Wonosari Barat Bengkalis - Syafrizal, Syafrizal; Syahmi Al-Haziq, Muhammad; Nuriyati, Tuti (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
This study uses a qualitative research method with a qualitative descriptive approach. Data collection techniques using interviews, observation, documentation, observation, and triangulation methods. Based on the results of the data analysis, it was concluded that Hadrah art has existed in Wonosari Tengah village since 2020. Initially, this art was used to spread religion. Along with the changing times, this art has become a spectacle for the entertainment of the local community. In this case, it includes several values such as beauty, morality, and religion. Because the values implied in this Hadrah art are to form people who believe in and fear Allah Subhanahu Wa Ta'ala, who have noble morals according to the example of the Prophet Muhammad Sallallahu Alaihi Wasallam, and become good citizens